Kepuasan Guru dalam Penggunaan E-Rapor di SMA Negeri 1 Pancung Soal Kabupaten Pesisir Selatan - Maharani, Inchi; Ahmad Sabandi (Global Action and Education for Society, 2024)
E-report is a web-based software for compiling reports on student competency achievements by educational unit level developed by the SMA curriculum sub-division. By using the e-report application, it can make it easier for teachers to input the grades obtained by students. The purpose of this study is to determine the level of satisfaction of e-Rapor users with the End-User Computing Satisfaction (EUCS) model as seen from the five variables, namely content, accuracy, form, ease of use, and timeliness. This research is a quantitative descriptive research, with a population of 84 sample teachers in this study using a non-probability sampling technique, namely saturated samples so that all populations are used as samples. Using the EUCS method, this research found that teacher satisfaction with the e-report at Pancung Soal 1 Public Senior High School (SMA) Pesisir Selatan regency was satisfied with the percentage of content 80.57%, accuracy 80.95% , format 80.05%, ease of use 80.00%, timeliness 80.60%